PELAKSANAAN PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM BERDASARKAN KURIKULUM 2013 DI MADRASAH ALIYAH NEGERI KARANGANYAR - Hidayati, Nur (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret, 2015)
The purposes of this research is to describe: (1) The understanding of the teacher history of Islamic culture about 2013 curriculum in MAN Karanganyar. (2) Learning planing the history of Islamic culture based on 2013 curriculum in MAN Karanganyar. (3) The implementation of learning history of Islamic culture based on curriculum 2013 in MAN Karanganyar. (4) The evaluation that was done by history of Islamic culture teacher on learning based on 2013 curriculum in MAN Karanganyar. (5) Supporting factor and constaints the teacher experienced in the implementation of learning the history of Islamic culture based on curriculum 2013 in MAN Karanganyar. This research used descriptive qualitaive method which emphasized the process and meaning of activity or state information. The research of the data collected by observation, interviews and document analysis. The test of the data used by trianggulation data and trianggulation method. In this research used interactive analysis model.The achievement of this research that found: (1) The teacher of the history of Islamic culture quite understanding enough of 2013 curriculum while in the implementation the teacher still having difficulty. (2) Planing the learning history of Islamic culture in MAN Karanganyar begins by the preparation of tools learning such as RPP based on syllabus 2013 curriculum. (3) The implementation of learning the history of Islamic culture in MAN Karanganyar devided into preliminary, core, closure and use a scientific approach is devided by the activity observe, ask, explore, associate, and communicate. (4) Evaluation of the learning is done by an assesment of the aspect of knowledge,skill and attitudes of learners. (5) Factor inhibiting learning the history of Islamic culture is the unavailability of the student book specialization the history of Islamic culture as a source of learning, the use of media that is not maximized, the state of students is different educational backgrounds and too detail teacher assesment techniques makes difficulty, supporting factor is the avability of supporting infranstructures learning adequate.